Acute Limb Arterial Ischemia Following Iliac Vein Stenting in the Setting of a Frozen Pelvis. (November 2022) - Trinidad, Bradley; Berman, Scott S; Labropoulos, Nicos; Pacanowski, John; Yanquez, Federico; Chen, Winsor; Leon, Luis R
The authors report on a young patient with previous radiation to her pelvis who presented with acute limb ischemia following iliac vein stenting believed to be secondary to extrinsic iliac artery compression in the setting of a frozen pelvis. She underwent revascularization and a trans-femoral amputation, ultimately needing a femoral to femoral artery crossover bypass in order to achieve amputation stump healing. This case describes a potential arterial complication of venous stenting in a previously irradiated field.